2017
DOI: 10.1016/j.meegid.2017.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping CD8 + and CD4 + T-cell epitopes identification for the progression of epitope-based peptide vaccine from nucleocapsid and glycoprotein of emerging Rift Valley fever virus using immunoinformatics approach

Abstract: Rift Valley fever virus (RVFV) is an emergent arthropod-borne zoonotic infectious viral pathogen which causes fatal diseases in the humans and ruminants. Currently, no effective and licensed vaccine is available for the prevention of RVFV infection in endemic as well as in non-endemic regions. So, an immunoinformatics-driven genome-wide screening approach was performed for the identification of overlapping CD8+ and CD4+ T-cell epitopes and also linear B-cell epitopes from the conserved sequences of the nucleoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 98 publications
1
39
0
Order By: Relevance
“…However, we identified the potential T-cell epitopes from the most antigenic polyprotein, as they play a key role in the creation of a defensive immune response against different pathogenic infections [ 75 ]. Various successful studies have been performed for the epitope-based peptide vaccine design against West Nile virus [ 76 ], Zika virus [ 77 ], dengue virus [ 78 ], Chikungunya virus [ 79 ], Rift valley fever virus [ 80 ], shigellosis [ 81 ], and so on. Primarily, we identified 146 epitopes in total using 12 supertypes (A1, A2, A3, A24, A26, B7, B8, B27, B39, B44, B58, and B62) and selected 128 epitopes based on the highest combined score.…”
Section: Discussionmentioning
confidence: 99%
“…However, we identified the potential T-cell epitopes from the most antigenic polyprotein, as they play a key role in the creation of a defensive immune response against different pathogenic infections [ 75 ]. Various successful studies have been performed for the epitope-based peptide vaccine design against West Nile virus [ 76 ], Zika virus [ 77 ], dengue virus [ 78 ], Chikungunya virus [ 79 ], Rift valley fever virus [ 80 ], shigellosis [ 81 ], and so on. Primarily, we identified 146 epitopes in total using 12 supertypes (A1, A2, A3, A24, A26, B7, B8, B27, B39, B44, B58, and B62) and selected 128 epitopes based on the highest combined score.…”
Section: Discussionmentioning
confidence: 99%
“…2(b)). The population coverage analysis revealed that the MHC HLA alleles corresponding to predicted T-cell vaccine candidates are well & widely distributed throughout the world, which is a robust property of rational vaccine design 57,58 .…”
Section: Prediction Of Linear B-lymphocyte Vaccine Candidatesmentioning
confidence: 99%
“…Different HLA alleles, as well as their expression, are sensationally distributed at various frequencies in diverse ethnicities [38]. Hence, the HLA-alleles distribution among the world population is crucial for successful multi-epitope vaccine development.…”
Section: Estimation Of Population Coveragementioning
confidence: 99%